Implementasi Perlindungan Hukum Terhadap Anak dalam Kasus Perceraian berdasarkan Undang Undang Nomor 35 Tahun 2014 (Studi Kasus Pengadilan Agama Binjai) - ahmad zaki; Suci Ramadhona (Program Studi Hukum Keluarga Islam Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2025)
The rising divorce rate in Indonesia has serious implications for the fulfillment of children's rights, particularly regarding the psychological aspects, which are often neglected. This study aims to analyze the implementation of legal protection for children, with a focus on their psychological needs and the principle of the best interest of the child, in divorce cases at the Binjai Religious Court. The research method employed is normative-juridical, utilizing a statutory approach, a conceptual approach, and an analysis of Islamic law perspectives concerning hadhanah (child custody) and child support (nafkah). Data was sourced from regulations, academic literature, and court case documents. The findings reveal that although judges have referred to child protection provisions (such as those in Law Number 35 of 2014), considerations of children's psychological aspects remain declarative and have not become substantive in court rulings. The main obstacles include judges' limited understanding of family psychological dynamics, the scarcity of counseling support services within the court environment, and low parental awareness. It is concluded that strengthening both regulations and judicial practices is necessary to ensure comprehensive child protection in the aftermath of divorce.